The effect of recent consumption of caffeine-containing foodstuffs on neuropsychological tests in the elderly. - Lesk, V; Honey, T; de Jager, C (2009)
We investigated the effect of recent intake of caffeine-containing foodstuffs (CCFS) on a group of elderly participants (age range 67-95 years) on a series of neuropsychological tests. There was no significant effect of CCFS intake on performance in any of the tests in the battery used. However, a significant interaction effect was found between age and CCFS consumption on scores of some neuropsychological tests. In these tests, participants with recent consumption of CCFS show a linear decrease in performance with increasing age, a pattern not seen for those that have no CCFS in their system. Accuracy in the neuropsychological assessment is of great importance when determining whether someone has a cognitive impairment or early Alzheimer's disease. We therefore propose that recent consumption of CCFS should be taken into account when scoring the neuropsychological assessment.